Inhibitory gain modulation of defense behaviors by zona incerta - Xiao-lin Chou (Nature Portfolio, 2018)
Zona incerta (ZI) is an inhibitory subthalamic nucleus with diverse connectivity yet its functional importance has not been extensively studied. Here the authors report that ZI receives mPFC input and can modulate both innate and learned defensive behaviors via its inhibitory projection to the PAG.